PENGENALAN PERANGKAT KOMPUTER PADA SISWA SEKOLAH DASAR MENGGUNAKAN AUGMENTED REALITY - Aristamy, I Gusti Ayu Agung Mas; Dharsika, Eka; Iswardani, Putu Risanti; Pascima, Ida Bagus Nyoman (Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
SD Negeri 4 Peguyangan is one of the schools in Bali that applies ICT learning. ICT learning is carried out offline in a computer laboratory room with 13 teaching aids. The number of teaching aids in the computer laboratory does not even exceed half of the number of students per class, which is at least 31 students. The limited teaching aids make the learning process in ICT subjects ineffective, so that many students still do not fully understand the functions and parts of computers. This study aims to create an application that uses Augmented Reality technology on an Android-based smartphone to help recognize computer hardware. This research starts from the stage of data collection, analysis of existing conditions, application design, application implementation and application testing using the blackbox texting method. This Augmented Reality Application for Introduction to Computer Devices for Elementary School Students has tutorial features, camera scans, info, about and exit. This AR Application Recognizing Computer Devices can help and facilitate learning for students of SDN 4 Peguyangan in recognizing the form and function of computer devices